Augment, Not Replace: Utilising AI Tools for Documentary Podcast Production - Tennant, Lewis (Auckland University of Technology (AUT) Library, 2026)
This project examines how emerging technologies are reshaping established media production practices within audio documentary storytelling. Despite podcasting’s growth as a cultural form, scholarship on podcast production remains limited, with much existing research focused on third-party analysis rather than creative practice. Addressing this gap, the project involved the production of a five-episode narrative documentary podcast alongside a critical evaluation of AI tools used across pre-production, production, and post-production workflows. The findings demonstrate that emerging technologies are most effective when augmenting, rather than substituting for, specialist human knowledge and judgement. ChatGPT 5.0 was useful for broad exploratory research and generating initial leads in unfamiliar fields but proved unreliable as a primary research tool for documentary pre-production, requiring a return to conventional research methods. During production—particularly in script development—the tool operated more successfully within a mixed-initiative workflow. However, the uneven quality and relevance of AI-generated material necessitated that creative and editorial decision-making remain firmly human-led. Overall, the project positions AI as an augmentative presence that both supports and constrains creativity and craft, reinforcing the centrality of human authorship in documentary podcast production.
Keywords: 3605 Screen and digital media; Practice-led research; Podcast production; Audio documentary; Human-AI co-creation; Audio production; Creative technology; New Zealand podcasting; AI podcast production